2016
DOI: 10.1007/s11356-016-6712-3
|View full text |Cite
|
Sign up to set email alerts
|

Health risk assessment of heavy metals in soil-plant system amended with biogas slurry in Taihu basin, China

Abstract: Biogas slurry is a product of anaerobic digestion of manure that has been widely used as a soil fertilizer. Although the use for soil fertilizer is a cost-effective solution, it has been found that repeated use of biogas slurry that contains high heavy metal contents can cause pollution to the soil-plant system and risk to human health. The objective of this study was to investigate effects of biogas slurry on the soil-plant system and the human health. We analyzed the heavy metal concentrations (including As,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…For men, the TCR of rocca, coriander, and parsley was 6.87 × 10 −3 , 7.33 × 10 −3 , and 7.60 × 10 −3 , while for women, it was 7.88 × 10 −3 , 8.51 × 10 −3 , and 8.82 × 10 −3 respectively. In a study involving coriander and other crops, Bian et al (2016) found a significantly higher CR and TCR than the acceptable level and concluded that As, Cd, and Cr poses cancer risks in the study area.…”
Section: Carcinogenic Riskmentioning
confidence: 87%
“…For men, the TCR of rocca, coriander, and parsley was 6.87 × 10 −3 , 7.33 × 10 −3 , and 7.60 × 10 −3 , while for women, it was 7.88 × 10 −3 , 8.51 × 10 −3 , and 8.82 × 10 −3 respectively. In a study involving coriander and other crops, Bian et al (2016) found a significantly higher CR and TCR than the acceptable level and concluded that As, Cd, and Cr poses cancer risks in the study area.…”
Section: Carcinogenic Riskmentioning
confidence: 87%
“…Previous studies have shown that appropriate use of biogas slurry can increase soil nutrients, enhance crop nutritional quality, reduce greenhouse gas emissions, decrease crop disease and have other benefits ( Terhoeven-Urselmans et al, 2009 ; Louro et al, 2013 ; Wang L. et al, 2018 ; Xu M. et al, 2019 ). However, the excessive application of biogas slurry will also cause some negative effects, such as the pollution of surface water and groundwater due to excessive nutrient input, the risk of heavy metal and organic pollutant accumulation in the soil, and the reduction of crop yield ( Bian et al, 2015 , 2016 ; Zhang et al, 2017 ; Cheng et al, 2018 ). Therefore, it is important and necessary to explore appropriate methods for biogas slurry application in agricultural systems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the kernels can also absorb large amounts of trace elements. Due to soil pollution in planting areas (e.g., due to sewage irrigation, improper fertilization, and excessive pesticides application), the occurrence of excessive contents of heavy metals in peanut production areas is frequent (22). Although some scholars have already investigated the heavy Abbreviations: Cu, copper; EU, European Union; Zn, zinc; WHO, World Health Organization; Pb, lead; USEPA, U.S. Environmental Protection Agency; Cr, chromium; IPI N , integrated pollution index; Cd, cadmium; RI, potential ecological risk index; Hg, mercury; BCF, biological enrichment factor; As, arsenic; TF, transfer factor; TN, total nitrogen; EDI, estimated daily intake; TP, total phosphorus; THQ, total hazard quotient; TK, total potassium; TTHQ, total target hazard quotient; OM, organic matter; PTDI, provisional tolerable daily intake; Avail.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the kernels can also absorb large amounts of trace elements. Due to soil pollution in planting areas (e.g., due to sewage irrigation, improper fertilization, and excessive pesticides application), the occurrence of excessive contents of heavy metals in peanut production areas is frequent ( 22 ). Although some scholars have already investigated the heavy metal pollution in the soils of peanut planting regions ( 18 , 21 , 23 ), no study could be found on the safety risk assessment of applying biogas slurry on the soil and peanut quality.…”
Section: Introductionmentioning
confidence: 99%